Spectral Evidence, Non -Spectral Acts Of Witchcraft, And Confession At Salem In 1692 - Craker, Wendel D. (The historical journal, 1997)
It is commonly asserted that people were hanged at Salem on charges of spectral appearance; and the way to avoid hanging was to confess. Non-spectral acts of witchcraft are regarded as inconsequential to the outcome of the trials. Yet it was the non-spectral acts which provided the one magnet that attracted attention from the court. No one charged only with spectral appearance was even tried. The reprieves granted to confessors were the last decisions the court was allowed to make. This profile provides evidence that the standard claims about the court of oyer and terminer's use of evidence are the reverse of what actually happened, and highlights a number of patterns that have gone unremarked, requiring fresh interpretations.